Political Actors in Oligarchy Power the phenomenon of a Single Candidate in the Implementation of Democracy in Regional Head Elections in Indonesia - Prajoko, Roso; Hartini, Sri; Nuryana, Arief (Budapest International Research and Critics University, 2021)
The number of single candididates against the empty box in every regional head election continues to increase, as a result of the decision of the Constitutional Court Number 100/PUU-XIII/2015. After this decision, it is as if the regional elections were held democratically. This process tends to be form of killing the democratic process, because it runs unfairly and equally. Likewise, political parties are considered to have failed in preparing a leader every five years. Although a single candidate is legally valid, and is regulated in Law No. 10 of 2016. However, political parties as entry points to democracy must maintain an equal and fair democratic process, not the political oligarchy that controls the party. This study aims to look at the role of a political actor in preparing local leader candidates and the factor of the occurrence of a single cindadate against the empty box. The method used is descriptive qualitative to describe social events that exist in society. The results of this research show that the role of a political actor is very important and powerful in Regional Head Elections in Indonesia.